Pengaruh Return on Asset (ROA), Return on Equity (ROE) dan Net Interest Margin (NIM) Terhadap Laba Per Saham Pada PT Bank Mega TBK Periode 2008-2024 - Maryam, Andriani; Aulia, Reva; Madaniah, Nailah; Putri, Marshanda Salsabila; Angwarmase, Maria Refyo Agnawenan; Sumantri, Fazhar (JURNAL ONLINE INSAN AKUNTAN; Vol 10 No 1 (2025): Jurnal Online Insan Akuntan (Juni 2025)DO - 10.51211/joia.v10i1.3493, 2025)
This study aims to explore the impact of financial metrics, such as Return On Asset (ROA), Return On Equity (ROE), and Net Interest Margin (NIM), on earnings per share of PT. Bank Mega Tbk. In this study, we adopt a quantitative approach and apply regression analysis as a method to analyze the data. The data used are taken from the company's annual report covering the period from 2008 to 2024, and processed using SPSS software. The findings of this study indicate that the independent variables ROA, ROE, and NIM have a significant effect on earnings per share. The regression model used in this study is proven to be valid, with a coefficient of determination reaching 0.756 and a significance level above 0.005. Thus, it can be concluded that the three independent variables have the most significant effect on Bank Mega's earnings per share.   Keywords :   Return on Assets, Return on Equity, Net Interest Margin, Earnings Per Share, PT Bank Mega Tbk.